2014
DOI: 10.4103/2231-0762.144575
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of bite forces in patients after treatment of mandibular fractures with miniplate osteosynthesis and internal locking miniplate osteosynthesis

Abstract: Aims and Objectives:The aim of present study was to compare the stability of fractured mandibular fragments under functional load, when fixed with conventional miniplate and internal locking miniplate.Materials and Methods:Bite force (in kg) recorded in twenty mandible fractured patients and fifty normal healthy individuals. Bite force was measured at incisor and molar regions. Comparative evaluation of bite force generated was performed between 10 cases treated with conventional miniplates and 10 cases treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 20 publications
3
18
0
1
Order By: Relevance
“…[16] observed that patients treated with locking plate/screw system postoperatively generated more bite force compared to those treated with conventional miniplate screw system. However, they have not highlighted the significance of their findings in statistical terms.…”
Section: Discussionmentioning
confidence: 99%
“…[16] observed that patients treated with locking plate/screw system postoperatively generated more bite force compared to those treated with conventional miniplate screw system. However, they have not highlighted the significance of their findings in statistical terms.…”
Section: Discussionmentioning
confidence: 99%
“…The reference lists of the selected papers and a hand search revealed one additional relevant paper. A total of 4 studies involving 130 patients 4 14 15 16 evaluated bite force and were included in the qualitative synthesis ( Fig. 1 ).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…One study presented the results through graphs, and it was not possible to extract the adequate statistical data for it. 15 The author was contacted by e-mail, but we could not obtain an answer. Therefore, only two studies 4 14 were included in the meta-analyses.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…ОРИГИНАЛЬНЫЕ СТАТЬИ теза предложены различные способы стимуляции процесса регенерации костной ткани [3]. Одним из таких способов является функциональная нагрузка, которая возможна при сохранении подвижности нижней челюсти и восстановлении сократительной активности поврежденных в результате травмы жевательных мышц [4] (жевательное давление в норме у мужчин на резцах 25-40 кг, на молярах 50-80 кг [5], при переломах нижней челюсти снижено до 2,23-3,2 кг на резцах и 7-12 кг на молярах [6,7]). Современные аппараты для компрессионно-дистракционного остеосинтеза не позволяют восстановить функциональную активность жевательных мышц, в связи с чем функциональную нагрузку при этом нельзя считать полноценной.…”
unclassified